Guillain-Barre syndrome in SARS CoV-2: Case series of uncommon neurological complication from tertiary care center, Bengaluru, South India - Mamatha Tittamegalapalya Ramalingaiah; Latha Venakataramanappa; Sumedha Swamy; Virender Singh; Vinutha Bagalur Srinivas Murthy (Asian Journal of Medical Sciences, 2023)
Coronavirus disease is an infectious disease caused by severe acute respiratory syndrome-coronavirus 2 virus. It predominantly affects respiratory system causing fever, cough, and breathlessness. But it can also affect central nervous system and peripheral nervous system. It is important that physicians keep a high index of suspicion for patients with neurologic symptoms following a recent or during COVID-19 infection. The low rate of initial diagnosis is alarming, as few of the percentage of patients with Guillain-Barre syndrome will develop respiratory muscle weakness requiring invasive ventilation. The ability to recognize the disease process could lead to life saving management. Furthermore, the initiation of therapy such as plasma exchange or intravenous immunoglobulin leads to an accelerated recovery time.